A Standardized Transcutaneous Electric Acupoint Stimulation for Relieving Tobacco Urges in Dependent Smokers. (5th June 2011) - Lambert, Caroline; Berlin, Ivan; Lee, Tat-Leang; Hee, Siew Wan; Tan, Audrey S. L.; Picard, David; Han, Ji Sheng
Abstract : The efficacy of acupuncture in smoking cessation, and its effect on the urge to smoke are unclear. We evaluated the effect of a standardized protocol of transcutaneous electric acupoint stimulations (TEAS) on alleviating the urge to smoke. Ninety-eight smokers were recruited in two double-blind studies. Participants abstained from smoking for 26 h, and were randomized to receive TEAS alternating between 2 and 100 Hz at four acupoints (LI4 and PC8, PC6 and TE5) at four different intensities (10, 5, Intermittent 5 or 0 mA). The urge to smoke was assessed by the Questionnaire of Smoking Urges (QSU-Brief). In Experiment 1, the 10 mA group ( n = 20) was compared with the 5 mA group ( n = 20); the increase in smoking urges did not differ significantly. Considering the possibility that 5 mA may be an active intervention, in Experiment 2, a true placebo (0 mA), and a proxy of placebo [Intermittent 5 mA (i5 mA)] were compared with 10 mA TEAS. In this experiment, 10 mA ( n = 20) TEAS showed a tendency to alleviate smoking urges compared with 0 mA ( n = 16), and i5 mA ( n = 19) TEAS. Only when the data of smokers with Fagerstöm Test for Nicotine Dependence score ≥5 were analyzed that the difference between the 10 mA group and the control group (0 and i5 mA) became significant. Based on these preliminary findings, we conclude that TEAS applied on the skin may antagonize the increase in urge to smoke in abstinent-dependent smokers. It seems warranted to assess the efficacy of TEAS in smoking cessation clinical trials involving a larger population of dependent smokers.